Impact of Spinal Cord Stimulation on Opioid Dose Reduction: A Nationwide Analysis. Issue 1 (31st August 2020) - Adil, Syed M; Charalambous, Lefko T; Spears, Charis A; Kiyani, Musa; Hodges, Sarah E; Yang, Zidanyue; Lee, Hui-Jie; Rahimpour, Shervin; Parente, Beth; Greene, Kathryn A; McClellan, Mark; Lad, Shivanand P
Abstract: BACKGROUND: Opioid misuse in the USA is an epidemic. Utilization of neuromodulation for refractory chronic pain may reduce opioid-related morbidity and mortality, and associated economic costs. OBJECTIVE: To assess the impact of spinal cord stimulation (SCS) on opioid dose reduction. METHODS: The IBM MarketScan® database was retrospectively queried for all US patients with a chronic pain diagnosis undergoing SCS between 2010 and 2015. Opioid usage before and after the procedure was quantified as morphine milligram equivalents (MME). RESULTS: A total of 8497 adult patients undergoing SCS were included. Within 1 yr of the procedure, 60.4% had some reduction in their opioid use, 34.2% moved to a clinically important lower dosage group, and 17.0% weaned off opioids entirely. The proportion of patients who completely weaned off opioids increased with decreasing preprocedure dose, ranging from 5.1% in the >90 MME group to 34.2% in the ≤20 MME group. The following variables were associated with reduced odds of weaning off opioids post procedure: long-term opioid use (odds ratio [OR]: 0.26; 95% CI: 0.21-0.30; P <  .001), use of other pain medications (OR: 0.75; 95% CI: 0.65-0.87; P <  .001), and obesity (OR: 0.75; 95% CI: 0.60-0.94; P  = .01). CONCLUSION: Patients undergoing SCS were able to reduce opioid usage. Given the potential to reduce the risks of long-term opioid therapy, this study lays the groundwork for efforts that may ultimately push stakeholders to reduce payment and policy barriers to SCS as part of an evidence-based, patient-centered approach to nonopioid solutions for chronic pain. Graphical Abstract: